Gay and bisexual men's awareness and knowledge of treatment as prevention: findings from the Momentum Health Study in Vancouver, Canada. Issue 1 (11th August 2015) - Carter, Allison; Lachowsky, Nathan; Rich, Ashleigh; Forrest, Jamie I; Sereda, Paul; Cui, Zishan; Roth, Eric; Kaida, Angela; Moore, David; Montaner, Julio SG; Hogg, Robert S
Abstract : Introduction: Awareness and knowledge of treatment as prevention (TasP) was assessed among HIV‐positive and HIV‐negative gay, bisexual and other men who have sex with men (GBMSM) in Vancouver, Canada. Methods: Baseline cross‐sectional survey data were analyzed for GBMSM enrolled, via respondent‐driven sampling (RDS), in the Momentum Health Study. TasP awareness was defined as ever versus never heard of the term "TasP." Multivariable logistic regression identified covariates of TasP awareness. Among those aware of TasP, men's level of knowledge of TasP was explored through an examination of self‐perceived knowledge levels, risk perceptions and short‐answer definitions of TasP which were coded as "complete" if three TasP‐related components were identified (i.e. HIV treatment, viral suppression and prevention of transmission). Information source was also assessed. Analyses were stratified by HIV status and RDS adjusted. Results: Of 719 participants, 23% were HIV‐positive, 68% Caucasian and median age was 33 (Interquartile range (IQR) 26, 47). Overall, 46% heard of TasP with differences by HIV status [69% HIV‐positive vs. 41% HIV‐negative GBMSM ( p <0.0001)]. In adjusted models: HIV‐positive GBMSM were more likely to have heard of TasP if they were Canadian born, unemployed, not using party drugs and had higher CD4 counts; HIV‐negative GBMSM were more likely to have heard of TasP if they were Caucasian (vs. Aboriginal), students, had higher education, a regular partner and multiple sexual partners. Among those aware of TasP 91% of HIV‐positive and 69% of HIV‐negative GBMSM ( p <0.0001) felt they knew "a lot" or "a bit in general" about TasP; 64 and 41% ( p =0.002) felt HIV treatment made the risk of transmission "a lot lower"; and 21 and 13% ( p <0.0001) demonstrated "complete" TasP definitions. The leading information source was doctors (44%) for HIV‐positive GBMSM and community agencies (38%) for HIV‐negative GBMSM, followed by gay media for both populations (34%). Conclusions: Nearly half of GBMSM in this study reported having heard of TasP, yet only 14% demonstrated complete understanding of the concept. Variations in TasP awareness and knowledge by HIV status, and key socio‐demographic, behavioural and clinical factors, highlight a need for health communication strategies relevant to diverse communities of GBMSM in order to advance overall TasP health literacy.